Evolving pattern of platelet P2Y12 inhibition in patients with acute coronary syndromes. (September 2014) - Joshi, Rajiv R.; Hossain, Rashed; Morton, Allison C.; Ecob, Rosemary; Judge, Heather M.; Wales, Clare; Walker, Jemma V.; Karunakaran, Arun; Storey, Robert F.
Abstract Dual antiplatelet therapy consisting of clopidogrel in addition to aspirin has previously been the standard of care for patients with acute coronary syndromes (ACS) but international guidelines have been evolving over the last 4 years with the introduction of prasugrel and ticagrelor. In October 2009, prasugrel was approved in the UK by the National Institute of Health and Clinical Excellence (NICE) for use in patients with ST-elevation myocardial infarction (STEMI) undergoing primary percutaneous coronary intervention (PCI), diabetic patients with non-ST-elevation (NSTE) ACS undergoing PCI and patients with stent thrombosis while other ACS patients were to continue receiving clopidogrel. Ticagrelor was approved in October 2011 by NICE for use in patients with moderate-to-high risk NSTE ACS and STEMI undergoing primary PCI and was recommended in preference to clopidogrel in European guidelines. These recommendations were adopted in our region, constituting a population of 1.8 million. We studied the effect of changing patterns of P2Y12 inhibitor usage on levels of platelet inhibition during maintenance therapy. Patients admitted to Northern General Hospital, Sheffield, with NSTE ACS or STEMI managed with primary PCI were enrolled over two periods of time: May 2010 to November 2011 (T1); and October 2012 to February 2013 (T2). Venous blood samples were obtained at 1 month after the onset of ACS. Light transmittance aggregometry (LTA) was performed and maximum aggregation response to ADP 20 μM was determined. A total of 116 patients were enrolled in T1 of whom 82 were receiving clopidogrel and 34 were receiving prasugrel. Twenty-nine patients were enrolled in T2, all of whom were receiving ticagrelor. Mean LTA results according to treatment with clopidogrel, prasugrel and ticagrelor were 57 ± 18%, 41 ± 20%, and 31 ± 12%, respectively. Prasugrel was associated with significantly lower platelet aggregation responses than clopidogrel (p < 0.001) and ticagrelor was associated with significantly lower platelet aggregation responses than both prasugrel (p = 0.015) and clopidogrel (p < 0.001). We conclude that international guidelines and NICE approval have led to increasing levels of P2Y12 inhibition in ACS patients in this UK centre between May 2010 and February 2013. Ticagrelor was associated with significantly greater P2Y12 inhibition than both clopidogrel and prasugrel during maintenance therapy.